THE ROLE OF HOSPITAL MARKETING MIX TO THE SELECTION OF THE HOSPITAL CONSUMER - Mardiah, Mardiah; Wahyu, Sulistiadi (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: The significant growth of hospital both of private and public hospital, additions requiring productive marketing strategy to sustained and increase consumers. Concept of 7p was developed from concept of 4p to create transparent communication between hospital and its customers. The given information will become the reason for customers to make their health related decision. This review is to see the role of each 7p concepst (person, place, promotion, physic, price, product and proses) in marketing and maintaining of hospitals. Methods: Full articles available at PubMed and Google Scholar, published from 2010-2018, and the student thesis were considered to explore the hospital marketing with mix marketing approach. Results: Of 412 full articles available at the searching tools, 10 articles have been selected for further discussion and analysis. From the results, it is noted that the 7p concepts of the costumer satisfactions present significant effects to the customers? trust to the hospital. Conclusion: This systematic review even only answer four out of seven P concept including proses, promotion, person and product, the findings may present the references to the hospital marketing in delivering the significant result for increasing customers? satisfaction.